THE ROLE OF LAZISMU MEDAN CITY PHILANTHROPY IN IMPROVING EDUCATION IN MUHAMMAD IYAH SCHOOLS IN MEDAN CITY - Yudha Pratama; Muhammad Qorib; Abd Rahman (FORUM PAEDAGOGIK, 2026)
This study aims to examine the contribution of philanthropic activities carried out by the Muhammadiyah Zakat, Infaq, and Shadaqah Institution (LAZISMU) of Medan City in improving the quality of education within Muhammadiyah schools. The background of this research is based on the urgency of optimizing zakat, infaq, and shadaqah (ZIS) funds to strengthen Islamic education that focuses on developing knowledgeable and virtuous generations. The study employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation involving LAZISMU administrators, school principals, teachers, and beneficiaries. The findings reveal that LAZISMU plays a significant role through various educational programs such as the Sang Surya Scholarship, Sekolah Cerah initiative, and Teacher Capacity Building Training. These programs have contributed to expanding educational access, enhancing student motivation, and improving teacher competence. Furthermore, transparent and accountable financial management has strengthened public trust in LAZISMU as an Islamic philanthropic organization committed to community empowerment. Overall, this study concludes that Islamic philanthropy has a strategic contribution in reinforcing the sustainability and independence of the Muhammadiyah education system.